Burhani Epistemology in The Scientific Development of Contemporary Pesantren - Ma'rufi, Anwar; Saifudin; Nisa’, Khorun; Muhajir (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This paper aims to analyze and prove that the scientific development tradition of contemporary pesantren has begun to adopt a system of rational thinking (burhānī), which so far is still considered incapable of breaking away from the bayānī and 'irfanī reasoning. The dominance of bayānī and 'irfanī reason was assessed by Muhammad Abid Al-Jabiri as the source of the decline of Arab-Islamic civilization. The study in this paper is included in the qualitative research category through a literature study whose data sources come from books and journals. The data analysis technique follows the pattern developed by Miles and Huberman with a philosophical approach. The results of this research found that the tradition of contemporary pesantren scientific development has begun to follow a system of thinking in the progressive burhānī epistemology. This is characterized by: (1) the transformation of the Islamic boarding school/pesantren education system driven by visionary Kiai and (2) the pattern of development of fiqh and ushul fiqh that is appropriate to the times following the principles contained in the burhānī thinking system. This study revises previous research, which assessed that the tradition of scientific development in pesantren still follows the system of thinking in bayānī and 'irfanī reasoning.